In vitro embryos production after oocytes treatment with forskolin - Paschoal, Daniela Martins [UNESP]; Maziero, Rosiára Rosária Dias [UNESP]; Sudano, Mateus José [UNESP]; Guastali, Midyan Daroz [UNESP]; Vergara, Luis Eduardo [UNESP]; Crocomo, Letícia Ferrari [UNESP]; Lima-Neto, João Ferreira de [UNESP]; Magalhães, Luis Carlos Oña [UNESP]; Monteiro, Bianca Andriolo [UNESP]; Rascado, Tatiana da Silva [UNESP]; Martins, Alício [UNESP]; Leal, Claudia Lima Verde; et al. (Cambridge University Press, 2015)
Summary The inhibition of nuclear maturation allows time for the oocyte to accumulate molecules that are important for embryonic development. Thus, the objective of this work was to evaluate the effect of blocking oocyte meiosis with the addition of forskolin, an efficient inhibitor of nuclear maturation, in in vitro maturation (IVM) medium. Forskolin was added to the IVM medium for 6 h at concentrations of 0.1 mM, 0.05 mM or 0.025 mM, then the oocytes were allowed to mature in drug-free medium for 18 h. The oocytes were assessed for the stage of nuclear maturation, the activity and distribution of mitochondria, oocyte ultrastructure, the number of viable cells and the apoptosis rate. After forskolin treatment, the oocytes were fertilized in vitro and cultured for 7 days. On day 7, the blastocyst rate, the ultrastructure, the number of intact cells and the apoptosis rate of the blastocysts were measured. No differences were observed for the stage of nuclear maturation of the oocyte, the mitochondrial activity and distribution, the blastocyst rate or total number of intact cells. However, a higher rate of apoptosis was observed in the blastocysts produced from oocytes blocked for 6 h with the higher concentration of forskolin (P < 0.05). We conclude that all the experimental groups reached the MII stage after the addition of forskolin and that the highest concentration of forskolin caused cellular degeneration without harming embryo production on the 7th day.
Keywords: Apoptosis; cAMP; Forskolin; IVM; Meiosis